2011
DOI: 10.1128/jcm.00779-11
|View full text |Cite
|
Sign up to set email alerts
|

Adhesin-Encoding Genes from Shiga Toxin-Producing Escherichia coli Are More Prevalent in Atypical than in Typical Enteropathogenic E. coli

Abstract: Four of six adhesin-encoding genes (lpfA, paa, iha, and toxB) from Shiga toxin-producing Escherichia coli strains were detected in typical and atypical enteropathogenic E. coli (EPEC) strains of various serotypes. Although the most prevalent gene was lpfA in both groups, paa was the only potential diarrhea-associated gene in atypical EPEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
0
19
0
3
Order By: Relevance
“…Almost all EPEC isolates (32 aEPEC and 1 tEPEC) were FAS positive (data not shown), one aEPEC isolate being the only exception (C144‐1) interacted with HeLa cells in an undefined pattern. LAL has been the most common adherence pattern detected among aEPEC , and the association of this feature with the ability to produce AE lesion has been found in association with diarrheal disease .…”
Section: Resultsmentioning
confidence: 97%
“…Almost all EPEC isolates (32 aEPEC and 1 tEPEC) were FAS positive (data not shown), one aEPEC isolate being the only exception (C144‐1) interacted with HeLa cells in an undefined pattern. LAL has been the most common adherence pattern detected among aEPEC , and the association of this feature with the ability to produce AE lesion has been found in association with diarrheal disease .…”
Section: Resultsmentioning
confidence: 97%
“…Intimins classified as beta1, epsilon1 and theta appear as the most frequent among aEPEC 78, 82, 83, 84, 85. In addition, some aEPEC strains bear adhesive-encoding genes that have been originally described in other DEC pathotypes and/or in extraintestinal pathogenic E. coli 79, 80, 82, 86, 87, 88. This observation suggests that aEPEC could employ additional adherence mechanisms besides the Tir-intimin interaction.…”
Section: Typical and Atypical Enteropathogenic E Colimentioning
confidence: 87%
“…Most aEPEC produce adherence patterns categorized as LA-like, with loosened microcolonies compared to those of the tEPEC LA pattern 12, 76, 77. In addition, some isolates express the aggregative (AA) or diffuse (DA) patterns of adherence, which are characteristics of the EAEC and DAEC pathotypes, respectively,20, 78 or adhere in undefined patterns or are non-adherent 20, 78, 79, 80. Remarkably, the epithelial cell adherence phenotype displayed by aEPEC is determined in prolonged assays (6 h) of bacteria-cell interaction 12, 76, 77.…”
Section: Typical and Atypical Enteropathogenic E Colimentioning
confidence: 99%
“…Other studies have shown the presence of adherence factors, other than EspA, in aEPEC (21,23,24), but none of them are ATs. Also, genes encoding proteins involved in biofilm formation (such as cah, ehaABCDJ, sab, and tibA) might be important in the persistence of both EPEC groups in the intestine.…”
mentioning
confidence: 99%